Implementation of Sustainable Development Goals by Polish universities - Gałat, Wioleta (Journal of Management and Financial Sciences, 2024)
In recent years, the issue of Sustainable Development Goals (SDGs) has received increasing interest from various entities in the socio-economic environment. Universities are recognized as entities that play a special role in popularizing the SDGs, and they are also expected to practically implement the SDGs within their own domains. Therefore, universities undertake tasks aimed at achieving the SDGs. The aim of this article is to examine the approach of Polish universities to the implementation of the SDGs by analyzing the content of four Directories of Social Responsibility Practices of Universities in Poland. Specifically, it is examined which SDGs Polish universities focus on, whether this focus changes over time, and whether universities that regularly report their best practices in these directories undertake other actions to achieve the SDGs.